(untitled) (Italian Journal of Public Health, 2007)
In recent years some of the most accredited health agencies have expressed a growing interest in Health Impact Assessment. This interest has arisen from the scientific evidence that demonstrates possible future health gains, especially in highly developed countries, can result not only from direct health interventions (both preventive and curative) but, above all, by the development of social, economic and environmental policies that take into consideration the policies impact on citizens’ health; many determinants do not originate from the health sector. Health is often central or the first ranked topic of each pending political decision. Strong and rigorous epidemiological approaches employed in health during the past decade or so have allowed us to identify causal relationships for diseases as well as health promoting factors. In the same way, epidemiological observation has provided us with a number of well-founded interpretative elements concerning the current situation, for example,health inequities among different social groups